AN OBSERVATION ON THE HISTORICAL EVOLUTION OF SOCCER FROM BEFORE CHRIST TO THE FIRST WORLD CUP - Muhammad Shahidul Islam; Md. Hamidur Rahman (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2021)
Soccer is one of the most widely played games in the world today. Millions of people are watching soccer games and its popularity has risen dramatically day by day. A variety of research works has been done on the history of football to satisfy people’s curiosity. Archaeological and historical evidence is a valuable resource for reconstructing soccer’s ancient history. Therefore, the current researchers would like to undertake an investigation that requires a review of the archaeological and historical literature. The primary goal of this scholarly qualitative research was to look at the historical evolution of soccer from Before the Common Era (BCE) to the first world cup. The literature was collected in this systematic qualitative analysis using online and offline methods. Present researchers found that between the Before Christ (BC) to the first World Cup, soccer underwent major changes, from violent to social. The rules of the game have been developed in line with the demand. During this time different types of football were played on different shapes of fields. No one had any headaches over a time frame. We must remember that today’s modern creative football stands on the golden history of the past.